Hiatos tecnológicos e padrões de comércio exterior nos BRIC (Brasil, Rússia, Índia e China) - Lopes Junior, Lúcio Baltazar (2008)
Considering the economic growth achieved by Brazil, Russia, India and China, countries that are part of the BRIC group, and the increase in their relevance on the world trade, this dissertation aims to analyze the evolution of their technological gap and to verify the relation with trade patterns and the influence of such gaps in the explanation of recent growth of these economies. In such a way, the work develops an analysis based on the evolution of the GDP growth; FDI; technological indexes based on patents USPTO, publication of scientific and technological papers and R&D expenditure; other than the sectorial trade patterns aggregated by technological intensities. The dissertation also estimate models of export determinants, where exports are classified as high, medium and low technology for each country, based on the Vector Autoregressive (VAR) econometric technique, using the Variance Decomposition Analysis and the Granger causality tests. The main results suggest the existence of a correlation between technological gap reduction and economic growth rates for these economies and a relation for technological improvements and positive changes in trade pattern favoring exports based on products with higher technology, indicating that the BRIC have faced important structural changes even considering their own specificities.